Method for evaluating carbon content in lithium sulfide and application of method
The reaction of lithium sulfide with phosphorus source and organic solvent is made of sulfide solid electrolyte, and its electronic conductivity is tested, which solves the problem of short-circuiting solid-state batteries caused by residual carbon in lithium sulfide, and achieves low-cost and accurate carbon content evaluation and improvement of solid-state battery performance.
Patent Information
- Application Number
- CN202510067823.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-16
AI Technical Summary
In the prior art, residual carbon during the preparation of lithium sulfide can easily lead to an increase in the electronic conductivity of the solid electrolyte, increasing the risk of short-circuiting solid-state batteries. At the same time, the existing testing methods are costly and have strict requirements on samples, making them inconvenient to detect.
By mixing lithium sulfide, phosphorus source and organic solvent, the precursor is obtained and then sintered to obtain a sulfide solid electrolyte, and the electronic conductivity test is performed. If the conductivity is higher than 1×10-7S/cm, it is determined that the carbon content in lithium sulfide is high and it is not suitable for preparing solid electrolytes.
This method can evaluate the carbon content in lithium sulfide at a low cost and accurately, determine whether it is suitable as a raw material for the preparation of solid electrolytes, and avoid the risk of short-circuiting of solid-state batteries.
Smart Images

Figure CN119881020A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a method for evaluating the carbon content in lithium sulfide and an application thereof. Background Art
[0002] Lithium sulfide (Li2S) is an important raw material for sulfide solid electrolytes. It is currently mainly prepared by reducing lithium sulfide precursors (one or more of lithium sulfate, lithium sulfite, lithium bisulfate, and lithium dithionate) at high temperatures using a reducing agent, wherein the reducing agent is generally a carbon-containing material (such as carbon, monosaccharides, and disaccharides). This method can obtain high-purity lithium sulfide.
[0003] However, the lithium sulfide prepared by this method will have a small amount of residual carbon remaining in the sulfide solid electrolyte, which can easily cause the electronic conductivity of the solid electrolyte and the solid-state battery made from it to increase, posing a short circuit risk in solid-state battery applications.
[0004] At present, the test method for carbon content in lithium sulfide is mainly measured by glow discharge plasma mass spectrometry. However, the equipment used in this method is expensive and has high requirements on the sample surface. It is necessary to ensure that the sample surface is clean and free of oxidation. In the actual testing process, the sample is prone to deterioration, which is not conducive to the detection of carbon content.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The first object of the present invention is to provide a method for evaluating the carbon content in lithium sulfide. By testing the electronic conductivity of a sulfide solid electrolyte prepared from lithium sulfide, the carbon content in the lithium sulfide can be evaluated, and then it can be determined whether the lithium sulfide is suitable as a raw material for preparing a sulfide solid electrolyte. The evaluation method is low in cost and suitable for popularization and use.
[0007] The second object of the present invention is to provide an application of a method for evaluating the carbon content in lithium sulfide in the preparation of sulfide solid electrolytes and solid-state batteries.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a method for evaluating the carbon content in lithium sulfide, comprising the following steps: mixing and reacting lithium sulfide, a phosphorus source and an organic solvent, and then performing solid-liquid separation to obtain a precursor; sintering the precursor to obtain a sulfide solid electrolyte; performing an electronic conductivity test on the sulfide solid electrolyte; if the electronic conductivity of the sulfide solid electrolyte is higher than 1×10 -7S / cm, it is judged that the carbon content in the lithium sulfide is high and is not suitable for preparing a sulfide solid electrolyte; otherwise, it is judged that the carbon content in the lithium sulfide is low and is suitable for preparing a sulfide solid electrolyte.
[0010] Further, the test method of the electronic conductivity test includes: the battery mold includes a shell having a cavity, a first electrode and a second electrode, wherein the first electrode and the second electrode have the same cross-sectional area, after the first electrode is inserted into the cavity, the sulfide solid electrolyte is added into the cavity, and then the second electrode is inserted into the cavity and pressurized so that the sulfide solid electrolyte forms a solid electrolyte layer and contacts the first electrode and the second electrode at both ends respectively, to obtain a battery cell; using an electrochemical workstation, the battery cell is tested by chronoamperometry to obtain a current-time curve; The current value corresponding to the last time point of the current-time curve is I, the voltage tested by the chronoamperometry is U, and the resistance R of the sulfide solid electrolyte is calculated, R=U / I, and the unit of R is Ω; the electronic conductivity σ of the sulfide solid electrolyte is calculated based on R, and the unit of σ is S / cm, σ=(1 / R)×D / A, wherein D is the thickness of the solid electrolyte layer in the battery cell, in cm; A is the contact area between the first electrode or the second electrode and the solid electrolyte layer, that is, the cross-sectional area of the first electrode or the second electrode, in cm 2 .
[0011] Furthermore, 140 to 160 mg of the sulfide solid electrolyte is added to the battery mold.
[0012] Furthermore, the voltage of the chronoamperometry test is 0.8-1.2V.
[0013] Furthermore, the chronoamperometry test time is 3 to 200 hours.
[0014] Furthermore, the sampling interval of the chronoamperometry test is 1 to 20 seconds.
[0015] Furthermore, the chemical formula of the sulfide solid electrolyte is xLi2S-(1-x)P2S5, wherein 0 <x<1。
[0016] Furthermore, the phosphorus source includes P2S5, P4S4, P4S5, P4S6, P4S7 and P4S 10 At least one of .
[0017] Furthermore, the organic solvent includes at least one of n-hexane, N-methylformamide, acetonitrile, tetrahydrofuran and methyl propionate.
[0018] Furthermore, the reaction temperature is 15-35°C.
[0019] Furthermore, the reaction time is 0.5 to 36 hours.
[0020] Furthermore, the reaction is carried out under an inert atmosphere.
[0021] Furthermore, the solid-liquid separation method includes: centrifuging at a speed of 10,000 to 15,000 r / min for 8 to 12 minutes.
[0022] Furthermore, a drying step is included before the sintering, and the drying temperature is 60-70°C.
[0023] Furthermore, the sintering temperature is 80-160°C.
[0024] Furthermore, the sintering time is 30 to 240 minutes.
[0025] Furthermore, the sintering is performed under an inert atmosphere.
[0026] The present invention further provides application of the method for evaluating the carbon content in lithium sulfide in preparing sulfide solid electrolytes and solid-state batteries.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The method for evaluating the carbon content in lithium sulfide provided by the present invention can evaluate the carbon content in lithium sulfide by testing the electronic conductivity of the sulfide solid electrolyte prepared from lithium sulfide, and then judge whether the lithium sulfide is suitable as a raw material for preparing the sulfide solid electrolyte. The evaluation method is low in cost and the judgment result is accurate. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a schematic diagram of the exploded structure of the battery mold provided by the present invention. DETAILED DESCRIPTION
[0031] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0032] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0033] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0034] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.
[0035] In a first aspect, the present invention provides a method for evaluating the carbon content in lithium sulfide, and also a method for judging whether lithium sulfide is suitable as a raw material for preparing a sulfide solid electrolyte, which specifically comprises the following steps:
[0036] Lithium sulfide, a phosphorus source and an organic solvent are mixed and reacted, and then the solid and liquid are separated to obtain a precursor; after the precursor is sintered, a sulfide solid electrolyte is obtained.
[0037] The electronic conductivity of the sulfide solid electrolyte is tested.
[0038] If the measured or calculated electronic conductivity of the sulfide solid electrolyte is higher than (i.e., greater than) 1×10 -7 S / cm, it is judged that the carbon content in the lithium sulfide is high and is not suitable for preparing sulfide solid electrolyte.
[0039] On the contrary (i.e. the electronic conductivity of the sulfide solid electrolyte is measured to be less than or equal to 10-7 S / cm), it is determined that the carbon content in the lithium sulfide is low and is suitable for preparing sulfide solid electrolyte.
[0040] The present invention can evaluate the carbon content in lithium sulfide by testing the electronic conductivity of the sulfide solid electrolyte prepared from lithium sulfide, and further judge whether the lithium sulfide is suitable as a raw material for preparing the sulfide solid electrolyte. The evaluation method has low equipment and labor costs, accurate judgment results, and can be widely promoted and used.
[0041] Specifically, the existing technology focuses more on the ionic conductivity of solid electrolytes. Currently, the ionic conductivity of solid electrolytes is generally around 10 -4 ~10 -3 S / cm, while less attention is paid to electronic conductivity. In traditional liquid batteries, electrons can only be transmitted between the positive and negative electrodes inside the battery through the external circuit and cannot be transmitted through the electrolyte. For solid electrolytes, electrons should also only be transmitted in the external circuit, and only ions are transmitted inside. Therefore, electronic conductivity should be 3 to 4 orders of magnitude lower than ionic conductivity, that is, it should be less than or equal to 10 -7 S / cm. If the electronic conductivity of the solid electrolyte is too high, it will self-discharge and cause the battery to short-circuit.
[0042] Therefore, the present invention determines whether the lithium sulfide used as the raw material for preparing the sulfide solid electrolyte is qualified by testing the electronic conductivity of the sulfide solid electrolyte prepared from lithium sulfide. This method is a method for assisting in controlling the quality of the raw material for preparing the sulfide solid electrolyte.
[0043] In some specific embodiments, the test method of the electronic conductivity test includes:
[0044] Preparing a battery mold: The battery mold includes a shell having a cavity, a first electrode and a second electrode, wherein the first electrode and the second electrode have the same size and cross-sectional area. The inner diameter of the cavity is the same as the outer diameter of the first electrode and the second electrode.
[0045] Insert the first electrode into the cavity, then add the sulfide solid electrolyte into the cavity, and then insert the second electrode into the cavity so that the sulfide solid electrolyte is located between the first electrode and the second electrode, and then pressurize so that the sulfide solid electrolyte forms a solid electrolyte layer and fully contacts the first electrode and the second electrode at both ends, respectively, to obtain a battery cell. Among them, the end surface of the first electrode is in full contact with the sulfide solid electrolyte, that is, the contact area between the first electrode and the solid electrolyte layer is the cross-sectional area of the first electrode. Similarly, the end surface of the second electrode is in full contact with the sulfide solid electrolyte, that is, the contact area between the second electrode and the solid electrolyte layer is the cross-sectional area of the second electrode.
[0046] like Figure 1 Shown is a schematic diagram of the exploded structure of the battery mold provided by the present invention.
[0047] The cell was tested by chronoamperometry using an electrochemical workstation to obtain a current-time curve.
[0048] The current value corresponding to the last time point of the current-time curve is I, the voltage tested by the chronoamperometry is U, and the resistance R of the sulfide solid electrolyte is calculated, R=U / I, and the unit of R is Ω.
[0049] The electronic conductivity σ of the sulfide solid electrolyte is calculated according to the R, where the unit of σ is S / cm, σ=(1 / R)×D / A, wherein D is the thickness of the solid electrolyte layer in the battery cell, in cm; A is the contact area between the first electrode or the second electrode and the solid electrolyte layer, that is, the cross-sectional area of the first electrode or the second electrode, in cm 2 .
[0050] In some specific embodiments, 140 to 160 mg (e.g., 145 mg, 150 mg, or 155 mg) of the sulfide solid electrolyte is added to the battery mold. If the amount of sulfide solid electrolyte added is too little, the electrolyte sheet will be too thin, the electrodes at both ends will be in direct contact and short-circuited, and no test results can be obtained; if the amount of sulfide solid electrolyte added is too much, part of the sulfide solid electrolyte powder cannot be pressed into sheets, and the actual sheet weight is less than the test added weight. It can be set specifically according to the shell size of the battery mold.
[0051] In some specific embodiments, the voltage of the chronoamperometry test is 0.8-1.2V, including but not limited to any point value of 0.8V, 0.9V, 1V, 1.1V, 1.2V or a range of values between any two of them.
[0052] In some specific embodiments, the time of the chronoamperometry test is 3 to 200 hours, including but not limited to any point value of 3h, 8h, 12h, 15h, 24h, 48h, 50h, 56h, 64h, 72h, 80h, 100h, 120h, 130h, 150h, 160h, 180h, 200h or any range value between two of them. The longer the test time, the more accurate the judgment result. If the time is too short, the current value may not converge to a stable result, so that an accurate electronic conductivity result cannot be obtained.
[0053] In some specific embodiments, the sampling interval for the chronoamperometry test is 1 to 20 s, including but not limited to the point value of any one of 1 s, 2 s, 3 s, 5 s, 6 s, 7 s, 8 s, 10 s, 12 s, 13 s, 15 s, 18 s, 20 s or the range value between any two of them.
[0054] In some specific embodiments, after adding the sulfide solid electrolyte into the battery mold and placing the test battery cell stably, apply pressure slowly to fix, clamp and prevent the test battery cell from shaking. After the pressure reaches 5 to 8 t and stabilizes, adjust the pressure to 0.5 to 1.0 t.
[0055] In some specific embodiments, the chemical formula of the sulfide solid electrolyte is xLi2S-(1-x)P2S5, where 0 < x < 1, and x is, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or 0.8.
[0056] It can be understood that the electronic conductivity of different types of sulfide solid electrolytes themselves does not differ much, but the carbon content has a greater impact on the electronic conductivity. Therefore, the method for evaluating the carbon content in lithium sulfide provided by the present invention can determine whether the corresponding lithium sulfide has too high a carbon content and whether it is suitable as a raw material for preparing sulfide solid electrolytes by measuring the electronic conductivity of different types of sulfide solid electrolytes.
[0057] In some specific embodiments, the phosphorus source includes at least one of P2S5, P4S4, P4S5, P4S6, P4S7 and P4S 10 in the following.
[0058] In some specific embodiments, the organic solvent includes at least one of n-hexane, N-methylformamide, acetonitrile, tetrahydrofuran and methyl propionate.
[0059] In some specific embodiments, the reaction is carried out at room temperature. For example, the reaction temperature can be 15 to 35 °C, such as 20 °C, 25 °C or 30 °C, but not limited thereto.
[0060] In some specific embodiments, the reaction time is 0.6 to 36 h, such as 1 h, 2 h, 4 h, 8 h, 12 h or 24 h.
[0061] In some specific embodiments, the reaction is carried out in an inert atmosphere.
[0062] In some specific embodiments, during the reaction process, zirconium beads are added and shaken with an oscillator. The collision of zirconium beads can provide energy to the reaction system and make the materials uniform.
[0063] It can be understood that, based on the target chemical formula of the sulfide solid electrolyte, the molar ratio of each element can be confirmed, and then the amount of lithium sulfide and phosphorus source can be determined.
[0064] It is understandable that the amount of organic solvent used has very little effect on the physical and chemical properties of the prepared sulfide solid electrolyte, so the amount of organic solvent used can be any conventional amount commonly used in the art, and the present invention is not limited to this.
[0065] In some specific embodiments, the solid-liquid separation method includes centrifugal separation, and the centrifugal separation method includes: centrifuging at a speed of 10000-15000 r / min for 8-12 minutes. Wherein, the speed includes but is not limited to any point value of 10000 r / min, 11000 r / min, 12000 r / min, 13000 r / min, 14000 r / min or any range value between two. The centrifugal time includes but is not limited to any point value of 8 min, 9 min, 10 min, 11 min, 12 min or any range value between two.
[0066] In some specific embodiments, the device used for solid-liquid separation includes a centrifuge.
[0067] In some specific embodiments, the sintering further includes a drying step, and the drying temperature is 60-70°C; including but not limited to any point value of 60°C, 62°C, 63°C, 65°C, 68°C, 70°C or a range value between any two of them.
[0068] In some specific embodiments, the sintering temperature is 80-160°C, for example, 90°C, 100°C, 110°C, 120°C, 130°C or 150°C.
[0069] In some specific implementations, the sintering time is 30 to 240 min, for example, 60 min, 120 min, 150 min or 200 min.
[0070] In some specific embodiments, the sintering is performed under an inert atmosphere.
[0071] In some specific embodiments, the inert atmosphere includes at least one of a nitrogen atmosphere and an argon atmosphere.
[0072] In a second aspect, the present invention provides application of the method for evaluating the carbon content in lithium sulfide in the preparation of sulfide solid electrolytes and solid-state batteries.
[0073] The method provided by the present invention prepares the lithium sulfide to be tested into a sulfide solid electrolyte and performs an electronic conductivity test. According to the electronic conductivity of the sulfide solid electrolyte, it can be judged whether the lithium sulfide is suitable for preparing the sulfide solid electrolyte. The method is simple, easy to implement, low in cost, easy to promote and use, and is conducive to preparing a solid electrolyte and a solid battery with excellent electrochemical properties.
[0074] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0075] Example 1
[0076] The method for evaluating the carbon content in lithium sulfide provided in this embodiment comprises the following steps:
[0077] (1) Preparation of sulfide solid electrolyte 3 / 4Li2S-1 / 4P2S5: Under the protection of nitrogen atmosphere, according to the ratio of the target chemical formula, add the lithium sulfide to be tested and the phosphorus source P2S5 to 30ml of n-hexane and stir and mix, add 15g of zirconium beads for shaking, react at 30°C for 12h, and obtain the precursor liquid after the reaction is completed. Use a centrifuge to centrifuge the above precursor liquid at a speed of 12000r / min for 10min to separate the solid and liquid to obtain the precursor. Dry the precursor at 70°C, and then sinter the dried precursor at 100°C for 3h under the protection of nitrogen atmosphere, and obtain the sulfide solid electrolyte after cooling.
[0078] (2) The electronic conductivity of the above-mentioned sulfide solid electrolyte is tested as follows: an electrochemical chronoamperometry test is performed using a simple battery mold, the simple mold comprising two electrodes of the same size (i.e., the same cross-sectional area) (i.e., a first electrode and a second electrode), a hollow cylindrical polyurethane battery case (i.e., a shell having a cavity), and the inner hollow diameter of the polyurethane battery case being the same as the diameter of the two electrodes.
[0079] The preparation method of the battery cell includes: first inserting an electrode into a polyurethane battery case; then adding 150 mg of the above-mentioned sulfide solid electrolyte into the polyurethane battery case, and then inserting another electrode and preliminarily compacting it. Then, it is placed stably on a hydraulic press, slowly pressurized to 6 tons and then slowly reduced to 1 ton. The pressure increase and decompression process ensures that the battery is fixed. After tightening, a solid electrolyte layer is formed to obtain a battery cell. Among them, the thickness of the solid electrolyte layer D = 0.0700 cm. The contact area between the first electrode or the second electrode and the solid electrolyte layer (that is, the cross-sectional area of the first electrode or the second electrode) A = 1.15 cm 2 .
[0080] The SP-150e electrochemical workstation was connected to the two electrodes of the battery cell prepared above with wires for chronoamperometry test. The chronoamperometry test parameters were: ① voltage: 1V; ② test time: 24h; ③ sampling interval: 10s. After the test was completed, the current-time curve was obtained.
[0081] The current value I corresponding to the last time point of the current-time curve is 6.25×10 -6 A, the voltage of the chronoamperometry test is U = 1V, and the resistance of the sulfide solid electrolyte is calculated as R = U / I = 1.6 × 10 5 Ω. And the electronic conductivity of sulfide solid electrolyte is calculated as σ = (1 / R) × D / A = 3.8 × 10 -7 S / cm.
[0082] The electronic conductivity of sulfide solid electrolyte is greater than 1×10 -7 S / cm, so it is determined that the carbon content in the above-mentioned lithium sulfide to be tested is too high and is not suitable for preparing sulfide solid electrolyte.
[0083] Example 2
[0084] The method for evaluating the carbon content in lithium sulfide provided in this embodiment is basically the same as that in Embodiment 1, except that the test parameters of the current-time curve are: ① voltage: 1.2V; ② test time: 48h; ③ sampling interval: 20s.
[0085] The current value I corresponding to the last time point of the current-time curve obtained in this embodiment is 5.73×10 -5 A, and thus the electronic conductivity of the sulfide solid electrolyte is calculated as σ = (1 / R) × D / A = 3.11 × 10 -6 S / cm.
[0086] The electronic conductivity of sulfide solid electrolyte is greater than 1×10 -7 S / cm, so it is determined that the carbon content in the above-mentioned lithium sulfide to be tested is too high and is not suitable for preparing sulfide solid electrolyte.
[0087] Example 3
[0088] The method for evaluating the carbon content in lithium sulfide provided in this embodiment is basically the same as that in Example 1, except that a sulfide solid electrolyte 1 / 2Li2S-1 / 2P2S5 is prepared, and the amounts of the lithium sulfide to be tested and the phosphorus source are adjusted according to the ratio of the target chemical formula.
[0089] The current value I corresponding to the last time point of the current-time curve obtained in this embodiment is 6.79×10 -5A, and thus the electronic conductivity of the sulfide solid electrolyte is calculated as σ = (1 / R) × D / A = 3.48 × 10 -6 S / cm.
[0090] The electronic conductivity of sulfide solid electrolyte is greater than 1×10 -7 S / cm, so it is determined that the carbon content in the above-mentioned lithium sulfide to be tested is too high and is not suitable for preparing sulfide solid electrolyte.
[0091] Example 4
[0092] The method for evaluating the carbon content in lithium sulfide provided in this embodiment is basically the same as that in Example 1, except that the lithium sulfide to be tested is prepared by a method different from that in Example 1, that is, the carbon content in the lithium sulfide to be tested used in this embodiment is different from that in Example 1.
[0093] The current value I corresponding to the last time point of the current-time curve obtained in this embodiment is 4.22×10 -7 A, and thus the electronic conductivity of the sulfide solid electrolyte is calculated as σ = (1 / R) × D / A = 2.39 × 10 -8 S / cm.
[0094] The electronic conductivity of sulfide solid electrolyte is less than 1×10 -7 S / cm, so it is determined that the carbon content in the above-mentioned lithium sulfide to be tested is low and suitable for preparing sulfide solid electrolyte.
[0095] The carbon content in the lithium sulfide used in each embodiment was tested by a glow discharge plasma mass spectrometer to verify whether the above-mentioned method for evaluating the carbon content in lithium sulfide is accurate. The carbon content test results are shown in Table 1.
[0096] Table 1 Carbon content test results
[0097]
[0098]
[0099] It can be seen from Table 1 that the carbon content in the lithium sulfide used in Examples 1 to 3 is relatively high, which does not meet the standard of sulfide electrolytes, and is accurate with the corresponding determination results. The carbon content in the lithium sulfide used in Example 4 is low, which meets the standard of sulfide electrolytes, and is accurate with the corresponding determination results.
[0100] This shows that the method for evaluating the carbon content in lithium sulfide provided by the present invention can evaluate whether lithium sulfide is suitable as a raw material for preparing sulfide solid electrolytes, and the judgment result is accurate.
[0101] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for evaluating the carbon content in lithium sulfide, characterized in that: The steps include: The lithium sulfide, phosphorus source and organic solvent are mixed and reacted, and then the solid and liquid are separated to obtain a precursor; the precursor is sintered to obtain a sulfide solid electrolyte; Conducting an electronic conductivity test on the sulfide solid electrolyte; If the electronic conductivity of the sulfide solid electrolyte is higher than 1×10 -7 S / cm, it is judged that the carbon content in the lithium sulfide is high and is not suitable for preparing a sulfide solid electrolyte; otherwise, it is judged that the carbon content in the lithium sulfide is low and is suitable for preparing a sulfide solid electrolyte.
2. The method for evaluating the carbon content in lithium sulfide according to claim 1, characterized in that: The test method of the electronic conductivity test includes: The battery mold comprises a shell having a cavity, a first electrode and a second electrode, wherein the first electrode and the second electrode have the same cross-sectional area, after the first electrode is inserted into the cavity, the sulfide solid electrolyte is added into the cavity, and then the second electrode is inserted into the cavity and pressurized so that the sulfide solid electrolyte forms a solid electrolyte layer and contacts the first electrode and the second electrode at both ends, respectively, to obtain a battery cell; Using an electrochemical workstation, the battery cell is tested by chronoamperometry to obtain a current-time curve; The current value corresponding to the last time point of the current-time curve is I, the voltage tested by the chronoamperometry is U, and the resistance R of the sulfide solid electrolyte is calculated, R=U / I, and the unit of R is Ω; The electronic conductivity σ of the sulfide solid electrolyte is calculated according to the R, where the unit of σ is S / cm, σ=(1 / R)×D / A, wherein D is the thickness of the solid electrolyte layer in the battery cell, in cm; A is the contact area between the first electrode or the second electrode and the solid electrolyte layer, that is, the cross-sectional area of the first electrode or the second electrode, in cm 2 .
3. The method for evaluating the carbon content in lithium sulfide according to claim 2, characterized in that: 140-160 mg of the sulfide solid electrolyte is added into the battery mold.
4. The method for evaluating the carbon content in lithium sulfide according to claim 2, characterized in that: At least one of the following conditions is met: (1) The voltage of the chronoamperometry test is 0.8 to 1.2 V; (2) The time of the chronoamperometry test is 3 to 200 hours; (3) The sampling interval of the chronoamperometry test is 1 to 20 seconds.
5. The method for evaluating the carbon content in lithium sulfide according to claim 1, characterized in that: The chemical formula of the sulfide solid electrolyte is xLi2S-(1-x)P2S5, where 0 <x<1。 6. The method for evaluating the carbon content in lithium sulfide according to claim 1, characterized in that: At least one of the following conditions is met: (1) The phosphorus source includes P2S5, P4S4, P4S5, P4S6, P4S7 and P4S 10 At least one of; (2) The organic solvent includes at least one of n-hexane, N-methylformamide, acetonitrile, tetrahydrofuran and methyl propionate.
7. The method for evaluating the carbon content in lithium sulfide according to claim 1, characterized in that: At least one of the following conditions is met: (1) The reaction temperature is 15 to 35° C.; (2) The reaction time is 0.5 to 36 hours; (3) The reaction is carried out under an inert atmosphere.
8. The method for evaluating the carbon content in lithium sulfide according to claim 1, characterized in that: The solid-liquid separation method comprises: centrifuging at a speed of 10,000 to 15,000 r / min for 8 to 12 minutes.
9. The method for evaluating the carbon content in lithium sulfide according to claim 1, characterized in that: At least one of the following conditions is met: (1) The sintering step also includes a drying step, and the drying temperature is 60 to 70° C.; (2) The sintering temperature is 80 to 160° C.; (3) The sintering time is 30 to 240 minutes; (4) The sintering is carried out under an inert atmosphere.
10. Use of the method for evaluating the carbon content in lithium sulfide according to any one of claims 1 to 9 in the preparation of sulfide solid electrolytes and solid-state batteries.
Citation Information
Patent Citations
Device and method for measuring the total organic carbon content of a sample fluid
CN110300891A
Solid electrolyte material and preparation method and application thereof
CN117174995A
Electric furnace steelmaking carbon content control system based on big data
CN118813903A
Method for detecting carbon coating integrity of lithium iron phosphate material
CN119224060A